Surface roughness and topography on denture base material fabricated with additive manufacturing techniques - Abizar Agung Wibawa; Budi Arifvianto; Rini Dharmastiti; Heribertus Dedy Kusuma Yulianto; Dibyo Pramono (Universitas Gadjah Mada, 2026)
Denture fabrication plays an important role in restoring oral functions, including mastication, speech, and esthetics, while also helping to prevent temporomandibular joint disorders. Conventional denture bases are commonly fabricated using heat-cured acrylic resin; however, this method still presents several limitations, including longer fabrication time, lower accuracy, and outcomes that are highly dependent on operator performance. The development of additive manufacturing technology offers several advantages, such as high reproducibility, improved accuracy in producing complex geometries, a more efficient digital workflow, and reduced material waste. This study investigated the effect of additive manufacturing using digital light processing (DLP) on the surface roughness and topography of denture bases fabricated with different printing layer thicknesses (50 μm and 100 μm), compared with conventional heat-cured acrylic resin bases. Disc-shaped samples with a diameter of 5 mm and a thickness of 2 mm were analyzed for surface roughness using a profilometer along a 2 mm straight line, while surface topography was observed using scanning electron microscopy (SEM). The results showed significant differences in surface roughness among the groups, where the additive manufacturing group with a 50 μm layer thickness exhibited the smoothest surface (0.96±0.26 μm), followed by the conventional heat-cured group (1.75±0.31 μm), while the additive manufacturing group with a 100 μm layer thickness showed the highest roughness value (4.27±0.55 μm). SEM analysis also revealed crater-like surface defects correlated with variations in layer thickness. These defects were observed more frequently in the additive manufacturing group with a 100 μm layer thickness compared with the 50 μm layer thickness group. These findings confirm the importance of additive manufacturing parameters in determining the final properties of denture bases and indicate the potential for optimizing fabrication techniques to achieve improved denture outcomes.